(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role and effectiveness of interactive methods in teaching future teachers to resolve pedagogical conflicts. Theoretical and methodological approaches to integrating interactive methods into the pedagogical education system, their content structure, and their didactic conditions are considered. The author analyzes the classification of interactive methods used in resolving pedagogical conflicts, the stages of their implementation, and the criteria for evaluating their effectiveness.